Use of anti tumor necrosis factor-alpha monoclonal antibody for ulcerative jejunoileitis - SEVEN, GÜLSEREN; Seven, GÜLSEREN; Assaad, Adel; Biehl, Thomas; Kozarek, Richard A. (My University, 2012)
Ulcerative jejunoileitis is an uncommon clinical syndrome consisting of abdominal pain, weight loss associated with diarrhea, and multiple inflammatory ulcerations and strictures of the small bowel. Ulcerative jejunoileitis can complicate established celiac disease or develop in patients de novo. Increased levels of tumor necrosis factor-alpha (TNF-alpha) in the small intestine of patients with untreated celiac disease are associated with a role in the immune pathogenesis of this disorder. No specific therapy has been shown to change the course of ulcerative jejunoileitis. We report a case of severe ulcerative jejunoileitis previously unresponsive to traditional therapies, including high dose corticosteroids and cyclosporine. The patient had a dramatic resolution of symptoms and a complete normalization of endoscopic findings after anti-TNF-alpha monoclonal antibody, infliximab (Remicade (R)). (c) 2012 Baishideng. All rights reserved.